2010
DOI: 10.1038/mp.2010.119
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression patterns in the hippocampus and amygdala of endogenous depression and chronic stress models

Abstract: The etiology of depression is still poorly understood, but two major causative hypotheses have been put forth: the monoamine deficiency and the stress hypotheses of depression. We evaluate these hypotheses using animal models of endogenous depression and chronic stress. The endogenously depressed rat and its control strain were developed by bidirectional selective breeding from the Wistar–Kyoto (WKY) rat, an accepted model of major depressive disorder (MDD). The WKY More Immobile (WMI) substrain shows high imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
164
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(173 citation statements)
references
References 87 publications
(97 reference statements)
6
164
0
3
Order By: Relevance
“…Such approaches have been previously used to investigate the molecular alterations induced by ADs in the hippocampus and other brain regions of naive animals (Conti et al, 2007;Gaska et al, 2012;Korostynski et al, 2013;Landgrebe et al, 2002;Lee et al, 2010;Sillaber et al, 2008;Surget et al, 2009;Takahashi et al, 2006); interpretation of these studies is, however, limited by the fact that treatment of individuals who do not display signs of depressive-like behavior is not comparable to a pathological context (Cryan and Slattery, 2007). Previous comparable studies relied on measures of a single behavioral index measurement (Drigues et al, 2003;Nakatani et al, 2004), while others using multidimensional animal models of depression focused on a single class of AD (Andrus et al, 2012;Datson et al, 2012;Lisowski et al, 2013;Surget et al, 2009) or two monoaminergic ADs (Malki et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Such approaches have been previously used to investigate the molecular alterations induced by ADs in the hippocampus and other brain regions of naive animals (Conti et al, 2007;Gaska et al, 2012;Korostynski et al, 2013;Landgrebe et al, 2002;Lee et al, 2010;Sillaber et al, 2008;Surget et al, 2009;Takahashi et al, 2006); interpretation of these studies is, however, limited by the fact that treatment of individuals who do not display signs of depressive-like behavior is not comparable to a pathological context (Cryan and Slattery, 2007). Previous comparable studies relied on measures of a single behavioral index measurement (Drigues et al, 2003;Nakatani et al, 2004), while others using multidimensional animal models of depression focused on a single class of AD (Andrus et al, 2012;Datson et al, 2012;Lisowski et al, 2013;Surget et al, 2009) or two monoaminergic ADs (Malki et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…FoxOs have been linked to skeletal muscle atrophy and control of cardiomyocyte size in numerous models (Sandri et al, 2004;Skurk et al, 2005) observed in major depression most commonly occur in the raphe nuclei, nucleus accumbens, anterior cingulated cortex, amygdala and hippocampus (Goffer et al, 2013;Tripp et al, 2011;Underwood et al, 1999;Andrus et al, 2012), but we still need to elucidate whether the change of FoxOs and their related signal pathways could be altered in region specific manner.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…In a related study, Vidal et al (2011) found that better coping strategies might make Sprague Dawley rats more resilient to social defeat stress than Wistar rats as measured in fear-and anxiety-based domains 31 . Strain-dependent responses to other physical stressors such as restraint or CMS have been shown, underscoring the role of complex genetics in regulating risk and resilience to chronic stress [32][33][34] .…”
Section: Definition Of Resilience In Animalsmentioning
confidence: 99%